A novel BMPR2 mutation in a patient with heritable pulmonary arterial hypertension and suspected hereditary hemorrhagic telangiectasia: A case report. Issue 31 (31st July 2020) - Ye, Fanhao; Jiang, Wenbing; Lin, Wei; Wang, Yi; Chen, Hao; Zou, He; Huang, Shiwei; Zhu, Ning; Han, Sisi
Abstract: Rationale: BMPR2 mutation is the most common cause of heritable pulmonary arterial hypertension (HPAH), but rare in hereditary hemorrhagic telangiectasia (HHT). ACVRL1, ENG and SMAD4 are the most common gene mutations reported in HPAH with HHT. Patient concerns: We report a 11-year-old boy with a definite diagnosis of pulmonary hypertension and suspected HHT with recurrent epistaxis. The results of gene detection showed that there was a nosense mutation in BMPR2 . The results of gene detection of ACVRL1, ENG and SMAD4 were normal. Diagnoses: Heritable pulmonary arterial hypertension with suspected hereditary hemorrhagic telangiectasia. Interventions: Patient was treated with ambrisentan 2.5 mg qd. About a month later, the patient developed massive gastrointestinal bleeding and sudden convulsions. The patient's vital signs were stable after symptomatic treatment. Outcomes: After discharging from hospital, the patients continued to take ambrisentan. No epistaxis or gastrointestinal bleeding was found in one month of follow-up, but the symptoms of chest tightness were not significantly alleviated. Lessons: BMPR2 with a nonsense mutation is more likely to cause HPAH with HHT and are more likely to be life-threatening.